2015
DOI: 10.4236/jct.2015.614126
|View full text |Cite
|
Sign up to set email alerts
|

BASANT, a Polyherbal Safe Microbicide Eliminates HPV-16 in Women with Early Cervical Intraepithelial Lesions

Abstract: Carcinoma cervix is a major cancer of women killing 510,000 women every year worldwide. Human papilloma virus (HPV) infection of cervical cells initiates the transformation of the cervical cells to malignant stage. HPV-16 is the most frequent type of HPV causing these changes. We report here the elimination of HPV-16 from the infected cells of all (11/11) women positive for HPV-16 by 30 intra-vaginal intakes of BASANT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…All the 11 HPV-infected women with low-grade cervical lesions enrolled in a placebo-controlled phase I trial with basant, cleared HPV-16 infection upon basant application ( Supplementary Table S1 , curcumin-based formulation no.3) [ 156 ].…”
Section: Plant Extracts Mixturesmentioning
confidence: 99%
“…All the 11 HPV-infected women with low-grade cervical lesions enrolled in a placebo-controlled phase I trial with basant, cleared HPV-16 infection upon basant application ( Supplementary Table S1 , curcumin-based formulation no.3) [ 156 ].…”
Section: Plant Extracts Mixturesmentioning
confidence: 99%
“…Two botanical formulations called, respectively, “Basant”, made of purified curcumin and saponins mixed to Emblica officinalis and Aloe vera extracts and Mentha citrata oil [ 143 ], and “Praneem”, composed by purified saponins, extracts from Azadirachta indica, Emblica officinalis , and Aloe vera mixed to Mentha citrata oil, have been shown able to block transfer of HPV16 pseudovirions in HeLa cells [ 143 , 152 ].…”
Section: Plant Metabolites Targeting Hpv Tumorsmentioning
confidence: 99%
“…Subsequently, a phase I/II clinical trial demonstrated that intra-vaginal administration of either curcumin capsules or Basant cream in HPV-infected women (without high grade CIN), was able to induce higher infection clearance rate (87.7% for Basant cream, 81.3% for curcumin capsules) than untreated patients (73.3%) [ 172 ]. Basant administration cleared HPV16 infection in 100% of patients (i.e., 11 HPV-infected women with low grade cervical abnormalities) recruited in a more recent study [ 143 ].…”
Section: Plant Metabolites Targeting Hpv Tumorsmentioning
confidence: 99%
“…What was amazing was that every woman (11/11) who used BASANT for 30 nights, had no HPV-16 in their cervical cells. Pap smear, which was abnormal to begin with, became normal in each case [3]. Thus BASANT can be extremely helpful to women to get rid of infection of HPV-16 in their cervical cells at early stages of CIN I, II, so long as the virus is not integrated in the host genome.…”
Section: Anti-hiv Action Of Basantmentioning
confidence: 99%